2020
DOI: 10.1002/solr.202000566
|View full text |Cite
|
Sign up to set email alerts
|

2D Materials as Electron Transport Layer for Low‐Temperature Solution‐Processed Perovskite Solar Cells

Abstract: Low‐temperature solution‐processed perovskite solar cells (PSCs) based on organic–inorganic hybrid perovskites have emerged as a low‐cost and high‐efficiency thin‐film photovoltaic technology. The reported power conversion efficiency (PCE) of laboratory produced PSCs with an active area of less than 0.1 cm2 has already exceeded 25%, which, however, decreases significantly to about 16% for a large device area of about 100 cm2. Therefore, the scalability has become one of the most significant limits on successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Furthermore, they are critical to the scalability and stability of devices. In general, efficient PSCs have two key interfaces, such as the ETL/perovskite heterojunction interface and the perovskite/HTL interface, which should both ensure effective charge collection and separation [ 81 ]. Inefficient charge transport can result in inhomogeneous charge accumulation and significant interfacial recombination, whereas a high-quality ETL and HTL not only collects and transfers charge carriers, but also effectively separates charges and suppresses charge recombination.…”
Section: Applications Of Mxenes In Pscsmentioning
confidence: 99%
“…Furthermore, they are critical to the scalability and stability of devices. In general, efficient PSCs have two key interfaces, such as the ETL/perovskite heterojunction interface and the perovskite/HTL interface, which should both ensure effective charge collection and separation [ 81 ]. Inefficient charge transport can result in inhomogeneous charge accumulation and significant interfacial recombination, whereas a high-quality ETL and HTL not only collects and transfers charge carriers, but also effectively separates charges and suppresses charge recombination.…”
Section: Applications Of Mxenes In Pscsmentioning
confidence: 99%
“…), 10,13 2D perovskites, 11,14 and other emerging 2D layered materials have become the focus of the advanced photovoltaic field with their flexible structures and outstanding chemical, physical, and optoelectronic properties. 15,16 A plethora of recent reports has unambiguously demonstrated that 2D tungsten disulfide (WS 2 ) materials were used as charge transporting layers and/or interlayers in PSCs and organic solar cells (OSCs) due to their high transmittance, high mobilities, and tunable band gaps (band gaps in the range of 1.1-2.1 eV), which shows superior performance to other 2D semiconductors in improving the PCE, dark storage, illumination, and thermal stability. [17][18][19][20] Song et al utilized the high hole mobility of 2D WS 2 (approximately 116 cm 2 V À1 s À1 at room temperature) to replace the conventional organic PEDOT:PSS hole transporting layer (HTL), greatly improving the efficiency and stability of inverted planar PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…), 10,13 2D perovskites, 11,14 and other emerging 2D layered materials have become the focus of the advanced photovoltaic field with their flexible structures and outstanding chemical, physical, and optoelectronic properties. 15,16…”
Section: Introductionmentioning
confidence: 99%
“… 1 In the two following decades, other covalent 2D architectures 2 and inorganic allotropes were developed, such as elemental 2D films 3 and metal–organic frameworks, 4 amongst others. 5 The intriguing properties of different 2D molecular systems are currently attracting great attention towards tackling important societal challenges such as green energy sourcing, 6 new-generation catalysts 7 and biomedical technologies. 8 Alternatively to static covalent and inorganic nanomaterials, supramolecular 2D assemblies allow controlled structural and functional reconfiguration.…”
Section: Introductionmentioning
confidence: 99%